Designing Credibility: How PT PLN Indonesia Power Unit PLTP Gunung Salak Practices an Objective Social Return on Investment (SROI) to Evaluate the CSR Program "Cakra Lumaku" - Muhammad Sulchan Fathoni; Topan Yuli Anggara; Tabita Titah Dewanti; Muchtar Muchtar (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The adoption of Social Return on Investment (SROI) as a mandatory component of Indonesia's PROPER environmental performance rating system has increased awareness of accountable CSR impact evaluation, yet its emphasis on a single ratio raises concerns that companies may prioritise compliance over genuine social impact. This article examines the Cakra Lumaku CSR programme implemented by PT PLN Indonesia Power Unit PLTP Gunung Salak as a case study of objective SROI practice within Indonesia's geothermal energy sector. Drawing on programme documentation and international SROI literature, the study identifies six evaluative principles that underpin credible impact assessment: materiality, methodological conservatism, transparency of assumptions, methodological triangulation, systematic reflection, and stakeholder verification. The analysis demonstrates how these principles are applied throughout the evaluation process, from outcome selection and conservative impact attribution to participatory validation, qualitative triangulation, and community learning. The resulting SROI ratio of 1.59, while modest compared with many reported Indonesian CSR cases, is interpreted as evidence of methodological restraint and evaluative credibility rather than limited programme success. The study finds that the maturity of SROI practice in Indonesia depends not on maximising reported returns, but on strengthening transparency, evidence-based evaluation, and multi-stakeholder participation throughout the evaluation process. This article contributes to the literature by documenting an underrepresented geothermal CSR case and proposing six practical principles for enhancing SROI credibility in high-stakes certification contexts.